Hypnobreastfeeding untuk Meningkatkan Pengeluaran Air Susu Ibu pada Masa Nifas - Arindiah Puspo Windari; Wiwi Rumaolat (FORIKES, 2022)
Breast milk is the nutrition that babies really need for growth, development and maintaining immunity. So research is needed which aims to determine the effect of hypnobreastfeeding techniques on the production of breast milk during the postpartum period. The design of this study was one group pretest-posttest, which involved 32 postpartum mothers, who were selected by total sampling technique. The smooth production of breast milk was measured through observation. In order to see the differences in the smoothness of milk production before and after being given the hypnobreastfeeding technique through education for postpartum mothers, an analysis was carried out using the Wilcoxon test, which had previously been tested for the normality of data distribution using the Shapiro Wilk test which showed that the data were not normally distributed. The p value of the Wilcoxon test was 0.000 so that it could be interpreted that there was a difference in the smoothness of breast milk production between before and after the intervention. It was concluded that the hypnobreastfeeding technique succeeded in expediting the release of breast milk during the postpartum period at the Taniwel Health Center.Keywords: breast milk; hypnobreastfeeding; childbirth ABSTRAK Air susu ibu merupakan nutrisi yang sangat dibutuhkan oleh bayi Untuk pertumbuhan, perkembangan dan mempertahankan imunitas. Maka diperlukan penelitian yang bertujuan untuk mengetahui pengaruh teknik hypnobreastfeeding terhadap pengeluaran air susu ibu pada masa nifas. Rancangan penelitian ini adalah one group pretest-posttest, yang melibatkan 32 ibu nifas, yang dipilih dengan teknik total sampling. Kelancaran pengeluaran air susu ibu diukur melalui observasi. Guna melihat perbedaan kelancaran produksi ASI sebelum dan sesudah diberikan teknik hypnobreastfeeding melalui edukasi pada ibu nifas, dilakukan analisis menggunakan uji Wilcoxon, yang sebelumnya telah diuji normalitas distribusi data menggunakan uji Shapiro wilk yang menunjukkan bahwa data tak terdistribusi normal. Nilai p dari uji Wilcoxon adalah 0,000 sehingga dapat ditafsirkan bahwaada perbedaan kelancaran pengeluaran air susu ibu antara sebelum dan sesudah intervensi. Disimpulkan bahwa teknik hypnobreastfeeding berhasil melancarkan pengeluaran air susu ibu pada masa nifas di Puskesmas Taniwel.Kata kunci: air susu ibu; hypnobreastfeeding; nifas